Comparison of the clinical efficacy and toxicity of nebulized polymyxin monotherapy and combined intravenous and nebulized polymyxin for the treatment of ventilator-associated pneumonia caused by carbapenem-resistant gram-negative bacteria: a retrospective cohort study - Wu, Zhenping; Zhang, Siying; Cao, Yelin; Wang, Qiyu; Sun, Keyuan; Zheng, Xia (Frontiers in Pharmacology, 2023)
Objective: To investigate the clinical efficacy and toxicity of nebulized polymyxin monotherapy and combined intravenous and nebulized polymyxin for the treatment of VAP caused by CR-GNB. Additionally, among patients treated with nebulized polymyxin monotherapy, we compared the clinical efficacy and toxicity of polymyxin B and polymyxin E.This study was a single-center, retrospective study. Included patients received aerosolized polymyxin for at least 72 hours with or without intravenous polymyxin for the management of CR-GNB VAP. The primary endpoint was clinical cure at the end of polymyxin therapy. Secondary endpoints included AKI incidence, time of bacteria-negative conversion, duration of MV after inclusion, length of stay in ICU, and all-cause ICU mortality.Results: 39 patients treated with nebulized polymyxin monotherapy were assigned to the NLpolymyxin group. 39 patients treated with nebulized polymyxin combined with intravenous use of polymyxin were assigned to the IV-NL-polymyxin group. Among the NL-polymyxin group, 19 2 This is a provisional file, not the final typeset article patients were treated with polymyxin B and 20 with polymyxin E. The clinical baseline characteristics before admission to the ICU and before nebulization of polymyxin were similar between the two groups. No differences were found between the two study groups in terms of microorganism distribution, VAP cure rate, time of bacteria-negative conversion, duration of MV after inclusion, length of stay in ICU and all-cause ICU mortality. Similarly, survival analysis did not differ between the two groups ( 2 =3.539，P=0.06). AKI incidence was higher in the IV-NLpolymyxin group. When comparing the clinical efficacy and toxicity to polymyxin B and polymyxin E, there was no difference between the two groups in terms of VAP cure rate, time of bacterianegative conversion, duration of MV after inclusion, length of stay in ICU, SOFA score, CPIS, AKI incidence and all-cause ICU mortality.Our study found that nebulized polymyxin monotherapy was non-inferior to combination therapy with intravenous polymyxin in treating CR-GNB-VAP. Furthermore, we observed no differences in clinical efficacy or related toxic side effects between polymyxin B and polymyxin E during nebulized polymyxin therapy as monotherapy. However, future prospective studies with larger sample sizes are required to confirm these findings.